Outlier Detection in VPN Authentication Logs for Corporate Computer Networks Access using CRISP-DM - Nilo Legowo; Wilyu Mahendra Bad (HighTech and Innovation Journal)
A Virtual Private Network (VPN) serves as a critical network access solution widely employed by corporations, enabling users to connect to company computer networks via a global infrastructure. Amid the ongoing Covid-19 pandemic, heightened reliance on computer network access has increased the vulnerability to data breaches by unauthorized parties. This necessitates a proactive approach from companies to safeguard data integrity, particularly by identifying abnormal access patterns and timestamps. This study aims to develop a model for detecting anomalous activities within authentication log data obtained from VPN usage. The dataset comprises log entries from September to November 2022, totaling 36,807 records, selected via a systematic sampling approach. Two key attributes, namely user ID and access time, are analyzed to trace access patterns. Employing the CRISP-DM method ensures a structured and efficient research process. The selection of the k value in the K-Nearest Neighbors (K-NN) method significantly impacts outlier detection and can be tailored to suit organizational requirements. By utilizing the K-Means algorithm for data clustering and K-NN for measuring inter-point distances, the study identifies outliers that warrant further investigation by the company. Integration of the proposed model into the company's big data platform facilitates real-time monitoring, enabling the security team to preemptively address potential threats and mitigate network access misuse. By enhancing awareness and responsiveness to information security risks, the model contributes to fortifying the company's cyber security posture amidst evolving digital landscapes.